Strategi Majelis Ulama Indonesia dalam Upaya Penerbitan Sertifikat Halal - Erlyta, Nency Ravica Lia; Sarbini, Ahmad; Herman, Herman (Tadbir: Jurnal Manajemen Dakwah, 2021)
This study aims to find out how the strategy of the West Java Indonesian Ulema Council is in the effort to issue a halal certificate which includes the formulation of strategies, implementation of strategies and evaluation of strategies. The method used in this research is descriptive method with a qualitative approach. The data collection used is observation, documentation study and interview techniques. The results of the study revealed that the strategy of the applied West Java Indonesian Ulema Council must support the policies and objectives of the institution formulated by developing missions, analyzing the strengths and weaknesses of the internal environment, analyzing the opportunities and threats of the external environment, then determining alternative strategies and choosing the right strategy. The coordinated implementation of the strategy is initiated by developing strategies that are in accordance with the culture of the institution, carrying out program activities including free halal certificates, halal expo titles, halal olympiad, halal certificate certification services, and halal care community. The halal certificate management system that is prepared neatly. West Java LPPOM MUI uses information systems to support activity programs. Evaluate building strategies that are in accordance with the demands and changes of the times. The evaluation system applied includes conducting auditor meetings, leadership meetings, special meetings, special coordination meetings, correcting actions and analyzing obstacles.